Keratometry repeatability in healthy and post-refractive surgery eyes: a comparison of two swept-source devices - Martínez-Albert, Noelia; Nieto-Fernández, Juan Carlos; García-Marqués, José Vicente (Graefe's archive for clinical and experimental ophthalmology, 2025)
To analyze the keratometry repeatability obtained with two swept-source devices in healthy and post-refractive surgery eyes. One hundred volunteers aged between 20 and 55 years were recruited for this study including both healthy and post-refractive surgery eyes. Patients included in the post-refractive surgery group underwent Laser-Assisted in Situ Keratomileusis (LASIK) or Photorefractive Keratectomy (PRK). Three consecutive measurements were taken with the IOLMaster 700 and Anterion and the evaluated measurements were simulated keratometry (Sim K), posterior keratometry (PK), and total keratometry (TK). Repeatability was assessed through the intra-subject standard deviation (S ), repeatability limit (R), and variability coefficient (CoV). Fifty patients were included in the control and post-refractive surgery groups, respectively. Similar repeatability was obtained for healthy and post-refractive surgery eyes using both devices. For IOLMaster 700, R ranged between 0.16 and 0.22 D for Sim K, 0.09-0.11 D for PK, and 0.18-0.24 D for TK. For Anterion, R ranged between 0.19 and 0.20 D for Sim K, 0.02 D for PK, and 0.20-0.21 D for TK. In general, the control group showed slightly higher S and R values than the post-refractive surgery group for TK and astigmatism measurements obtained with both devices. IOLMaster 700 and Anterion demonstrated good repeatability for simulated and total keratometry measurements obtained in healthy and post-refractive eyes. Moreover, the keratometry repeatability was comparable between healthy and post-refractive eyes using both SS-OCT devices.